Prevalence and predictors of alcohol use among HIVpositive Malawian adolescents attending selected AntiRetroviral Treatment clinics in Blantyre, Malawi - Kuyokwa, John (Department of Psychiatry and Mental Health, 2025)
Background: Alcohol use among adolescents living with HIV attending Anti-Retroviral Treatment clinics is a common occurrence in many low- and middle-income countries, yet data is scarce from Malawi. Adolescents living with HIV(ALHIV) are more likely to use alcohol because of psycho-social challenges associated with HIV status. The purpose of this study was to determine the prevalence and predictors of alcohol use among Malawian ALHIV attending selected Anti-Retroviral Treatment clinics in Blantyre, Malawi. Methods: A cross-sectional research study design was used and three hundred and seventy-six adolescents living with HIV (attending Anti-Retroviral Treatment clinics were recruited. The study participants were aged between 10-19 years. ALHIV participants were asked about their lifetime alcohol use and other psychosocial issues such as depression and anxiety symptoms, stigma, social support, peer pressure, post-traumatic stress disorder (PTSD), community factors, and family factors. For categorical and continuous variables, frequency distributions and descriptive statistics were computed. A multivariate logistic model was developed to determine factors associated with any life-time alcohol use. Results: The study found that the overall prevalence of lifetime alcohol use was 17.8% (n=67) and that other psycho-social problems were prevalent among ALHIV. Of the entire sample, 27.7% (n=104) reported depressive symptoms and 23.7% (n=89) reported symptoms of anxiety. Also, 70.5% (n=265) reported experiencing a traumatic event with 31.7%(n=119) reporting symptoms of PTSD. In the unadjusted model, seven variables were significantly associated with life-time alcohol use. Being female decreased the odds of reporting any lifetime alcohol use compared to being male (OR=0.51, 95% CI 0.29, 0.88). As age increased the odds of lifetime alcohol use also increased by 18% (OR=1.18, 95% CI 1.02, 1.31). Participants who completed secondary school had increased odds of any lifetime alcohol use by 100% compared to those who had completed primary school only (OR=2.00, 95% CI 1.16, 3.47). ALHIV with symptoms of PTSD had increased odds of any life time alcohol use by 85% (OR=1.85, 95% CI 1.08-3.18), while participants who reported having more social support from a significant other (OR=0.87, 95% CI 0.77, 0.98), family (OR=0.83, 95% CI 0.72, 0.97) or friends (OR=0.83, 95% CI 0.72, 0.96) were less likely to report any lifetime alcohol use. In the adjusted model, gender remained significantly associated with any lifetime alcohol use, where females were less likely to have used alcohol than male participants (OR=0.53, 95% CI 0.30, 0.94). Conclusion: This is the first study to show prevalence of any alcohol use among Malawian ALHIV attending selected Anti-Retroviral Treatment clinics in Blantyre, Malawi. The prevalence of any life-time alcohol use among this adolescent group was 18%. This study suggests that males were more likely to report lifetime alcohol use compared to females.. Arguably, male ALHIV in this study might have experienced psycho-social challenges which made them more at risk of alcohol use than females; this may be required to be explored further in the study context. The results of this study may inform future studies and policy in the formation of effective prevention and management of symptoms of common mental health conditions among ALHIV to improve wellbeing in this group of adolescents living with a chronic condition.